Neutrophil-Related Oxidants Drive Heart and Brain Remodeling After Ischemia/Reperfusion Injury - Carbone, Federico; Bonaventura, Aldo; Montecucco, Fabrizio (Frontiers in Physiology, 2020)
The inflammatory response associated with myocardial and brain ischemia/reperfusion injury (IRI) is a critical determinant of tissue necrosis, functional organ recovery, and long-term clinical outcomes. In the post-ischemic period, reactive oxygen species (ROS) are involved in tissue repair through the clearance of dead cells and cellular debris. Neutrophils play a critical role in redox signaling due to their early recruitment and the large variety of released ROS. Noteworthy, ROS generated during IRI have a relevant role in both myocardial healing and activation of neuroprotective pathways. Anatomical and functional differences contribute to the responses in the myocardial and brain tissue despite a significant gene overlap. The exaggerated activation of this signaling system can result in adverse consequences, such as cell apoptosis and extracellular matrix degradation. In light of that, blocking the ROS cascade might have a therapeutic implication for cardiomyocyte and neuronal loss after acute ischemic events. The translation of these findings from preclinical models to clinical trials has so far failed because of differences between humans and animals, difficulty of agents to penetrate into specific cellular organs, and specifically unravel oxidant and antioxidant pathways. Here, we update knowledge on ROS cascade in IRI, focusing on the role of neutrophils. We discuss evidence of ROS blockade as a therapeutic approach for myocardial infarction and ischemic stroke.